Exclusion e inclusion en la foresteria latinoamericana: hacia donde va la descentralizacion? - Larson, A.M.; Pacheco, P.; Toni, F.; Vallejo Larios, M. (CIFOR and IDRC, 2006)
Forestry decentralization offers new opportunities for participation in decision-making regarding natural resources and for greater local resource control. Yet previous research has found that decentralizations, at least in the way that they are implemented, may also have detrimental effects on forest-dependent peoples. CIFOR, with support from IDRC, carried out a study in 2005 to investigate the implications of these processes in Bolivia, Brazil, Guatemala, Honduras and Nicaragua. This book represents a synthesis of this research. Among other things, it finds that most gains in terms of decentralized decision-making have come from contractual arrangements between sub-national governments and forestry institutes and through certain land tenure policies. With regard to marginalized groups, the research found that forestry in general is not a sector in which small producers are able to improve their welfare without specific policies operating in their favor, and for decentralization to have a positive effect, it has to come hand in hand with other measures—particularly those that address structural inequities, such as property rights and access to financial resources and technologies. The book has three principal goals: to propose a theoretical framework to conceptualize more effectively the relationship among decentralization, governance and livelihoods; to assess the current state of forestry decentralizations in Latin America, with particular attention to the role of sub-national governments and the effects on “marginalized” forest-dependent groups; and to identify research and actions that could increase the benefits of decentralization for these groups.